2004
DOI: 10.1002/ijc.20343
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between HPV16 E7 protein level and cytokeratin 19

Abstract: The mechanisms employed by human papillomaviruses (HPVs) to control the replication of the viral genome and the expression of the viral genes are extremely complex and further complicated by the fact that the viral life cycle is intricately tied to the differentiation program of its host epithelial tissue. Indeed, HPV-induced immortalization of keratinocytes and disruption of the normal cytokeratin (CK) expression pattern progress pari passu during the stepwise process that preludes to squamous cell carcinoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Previous studies using such markers in HNSCC have suggested a low specificity (Kawamata et al, 1999;Hamakawa et al, 2000a), particularly because of false-positive results associated with benign epithelial rests in lymph nodes found in 1.6% of cervical nodes, but only in lymph nodes from level I (Gnepp, 2000;Hamakawa et al, 2000b). The assay used in the present study, that is, RT -PCR detection of CK19 mRNA, has been developed in our laboratory for the detection of occult carcinomatous cells in mediastinal lymph nodes in non-small-cell lung carcinoma (Saintigny et al, 2005) and by other teams in various carcinomas (Van Trappen et al, 2001;Inokuchi et al, 2003;Favia et al, 2004). The primers and probe for CK19 mRNA detection were designed to avoid the detection of the two known pseudogenes (Rund et al, 1999;Van Trappen et al, 2001;Saintigny et al, 2005) and we used real-time RT -PCR with the Taqman chemistry.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies using such markers in HNSCC have suggested a low specificity (Kawamata et al, 1999;Hamakawa et al, 2000a), particularly because of false-positive results associated with benign epithelial rests in lymph nodes found in 1.6% of cervical nodes, but only in lymph nodes from level I (Gnepp, 2000;Hamakawa et al, 2000b). The assay used in the present study, that is, RT -PCR detection of CK19 mRNA, has been developed in our laboratory for the detection of occult carcinomatous cells in mediastinal lymph nodes in non-small-cell lung carcinoma (Saintigny et al, 2005) and by other teams in various carcinomas (Van Trappen et al, 2001;Inokuchi et al, 2003;Favia et al, 2004). The primers and probe for CK19 mRNA detection were designed to avoid the detection of the two known pseudogenes (Rund et al, 1999;Van Trappen et al, 2001;Saintigny et al, 2005) and we used real-time RT -PCR with the Taqman chemistry.…”
Section: Discussionmentioning
confidence: 93%
“…Although a growing number of studies have reported a close link between CK7 or CK19 and HPV positive OPSCC, little is known about the roles played by CK7 and CK19 in the pathogenesis of HPV‐related SCC . However, a few studies have analyzed interactions between HPV16 E7 mRNA and CK7 and CK19 in cervical cancer cell lines . In particular, in SiHa cells containing CK7/CK19, CK19 promotes HPV16 E7 oncoprotein expression by binding to the 6‐mer peptide SEQIKA of CK7, which interacts with E7 mRNA and inhibits E7 mRNA translation …”
Section: Discussionmentioning
confidence: 99%
“…7,8,10 However, a few studies have analyzed interactions between HPV16 E7 mRNA and CK7 and CK19 in cervical cancer cell lines. [11][12][13] In particular, in SiHa cells containing CK7/CK19, CK19 promotes HPV16 E7 oncoprotein expression by binding to the 6-mer peptide SEQIKA of CK7, which interacts with E7 mRNA and inhibits E7 mRNA translation. [11][12][13] Tonsillar and uterine cervical SCCs share some histopathological and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, by interacting with a 6-mer amino acid peptide SEQIKA present at position 91–96 in the human Krt7 sequence, HPV E7 messenger RNA (mRNA) was shown to be protected/stabilized [39]. In addition, viral mRNA translation was presumed to be increased by Krt19 [40], another member of the keratin family overexpressed in both cervical and anal SC junctions [17,41]. Although these intriguing findings need to be confirmed, they support the hypothesis of a specific regulation of viral transcripts in SC junction cells leading to increased viral oncoprotein levels and, subsequently, to (pre)cancer development/progression.…”
Section: High Vulnerability Of Sc Junctions To Hpv Infection and (mentioning
confidence: 99%